Altitude and endurance athletes: effects of acute and chronic hypoxic exposure - Wehrlin, J. P. (The Norwegian School of Sport Sciences, 2008)
"How does altitude affect performance"? This question has been asked by athletes, coaches and sport scientists for many years. Most of the current interest in altitude and altitude training can be traced back to the 1968 Summer Olympic Games held in Mexico City at an elevation of 2300m. At the 1968 Olympics, sprinters and jumpers in the sport of track and field set several world records in the "thin air" of Mexico City, whereas the distance runners ran markedly slower compared with 1968 world records. Interestingly, athletes from countries with moderate altitude such as Kenya and Ethiopia won a relatively high percentage of medals in the middle and long distance races (153). Since then, interest in altitude and altitude training has continued to grow. More recently, important endurance competitions, such as the Olympic Games (Salt Lake 2002 and Torino 2006) have taken place at low (1000 - 2000m) and moderate (2000 - 3000m) altitudes making it important to acclimatize in an optimal way for the target altitude. Furthermore, new altitude training concepts have been introduced with the goal of utilizing altitude in order to improve endurance performance not only at altitude, but at sea-level as well.